Comparison between Field Research and Controlled Laboratory Research - Aziz, Hassan A. (Archives of Clinical and Biomedical Research, 2017)
Research is defined as the systematic inquiry in order to reach new conclusions or to confirm earlier findings. The research design plays a critical role in the validity of the collected data and its analysis and thus, the main findings of the research problem. This review article compares between two research designs; field research and controlled laboratory research. Whilst field research offers contextual data on settings, interactions, or individuals, controlled laboratory research is basic, repeatable, and efficient type of research that can be applied across a variety of disciplines.